2007
DOI: 10.1017/s1138741600006508
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Biases in Human Causal Learning

Abstract: The main aim of this work was to look for cognitive biases in human inference of causal relationships in order to emphasize the psychological processes that modulate causal learning. From the effect of the judgment frequency, this work presents subsequent research on cue competition (overshadowing, blocking, and super-conditioning effects) showing that the strength of prior beliefs and new evidence based upon covariation computation contributes additively to predict causal judgments, whereas the balance betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…For instance, studies have confirmed that a stimulus is more likely to be seen as a cause of an event if participants have prior knowledge about a mechanism by which the stimulus can cause the event (Bullock, Gelman, & Baillargeon, 1982;Lien & Cheng, 2000). Also, new evidence is interpreted in the light of old evidence for a certain relation (e.g., Maldonado, Catena, Perales, & Cándido, 2007); hence, both abstract and specific prior knowledge determine associative learning in a way consistent with propositional models.…”
Section: First Core Assumption: Associative Learning Effects Depend Omentioning
confidence: 99%
“…For instance, studies have confirmed that a stimulus is more likely to be seen as a cause of an event if participants have prior knowledge about a mechanism by which the stimulus can cause the event (Bullock, Gelman, & Baillargeon, 1982;Lien & Cheng, 2000). Also, new evidence is interpreted in the light of old evidence for a certain relation (e.g., Maldonado, Catena, Perales, & Cándido, 2007); hence, both abstract and specific prior knowledge determine associative learning in a way consistent with propositional models.…”
Section: First Core Assumption: Associative Learning Effects Depend Omentioning
confidence: 99%
“…We refer the reader to articles describing CTS [6,30] for full details about its architecture and its learning mechanisms. We have integrated the CMRules algorithm in CTS to give it the capability of finding the cause of learners' mistakes (the ability of finding causes is referred as "causal learning" in the cognitive science literature [31,32,33]). To do so, we have modified CTS so that it records each of its executions (interactions with learners during a training session) as a sequence in a sequence database.…”
Section: Application Of the Algorithm In An Intelligent Tutoring Agentmentioning
confidence: 99%
“…Furthermore, causal learning is the process through which we come to infer and memorize an event's reasons or causes based on previous beliefs and current experience that either confirm or invalidate previous beliefs [10]. In the context of CELTS, we refer to Causal Learning as the use of inductive reasoning to generalize causal rules from sets of experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of CELTS' Causal Learning Mechanism (CLM) is two-fold: 1) is to find causal relations between events during training sessions in order to better assist users; and 2) to implement partial procedural learning in CELTS' Behavior Network (BN) 1 , which is based on Maes' Behavior Network [11]. To implement CELTS' CLM, we draw inspiration from Maldonado's work [10] that defines three hierarchical levels of causal learning: 1) the lowest level, responsible for the memorization of task execution; 2) the middle level, responsible for the computation of retrieved information; and 3) the highest level, responsible for the integration of this evidence with previous causal knowledge.…”
Section: Introductionmentioning
confidence: 99%